Miniimonas arenae gen. nov., sp. nov., an actinobacterium isolated from sea sand - Ue, Harumi; Matsuo, Yoshihide; Kasai, Hiroaki; Yokota, Akira (International Journal of Systematic and Evolutionary Microbiology, 2011)
A Gram-positive, non-motile, coccoid- to rod-shaped, non-spore-forming bacterium, designated strain YM18-15T, was isolated from sea sand and studied using a polyphasic taxonomic approach. Strain YM18-15T grew under both aerobic and anaerobic conditions. The cell-wall peptidoglycan type was A4β and ornithine was the diagnostic diamino acid. The polar lipids were phosphatidylglycerol, diphosphatidylglycerol, phosphatidylinositol and an unknown phospholipid, MK-8(H4) was the major menaquinone and the predominant fatty acids were anteiso-C15 : 0 and C16 : 0. The DNA G+C content was 74.2 mol%. High 16S rRNA gene sequence similarities (96.3–97.3 %) were found with the sequences of the type strains of the three genera of the family Beutenbergiaceae. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain YM18-15T formed a clade with Serinibacter salmoneus, Salana multivorans and Beutenbergia cavernae. Strain YM18-15T differed from these three type strains in chemotaxonomic characteristics and in 16S rRNA gene signature nucleotides. Based on genetic and chemotaxonomic evidence, it is suggested that strain YM18-15T represents a novel species of a new genus within the family Beutenbergiaceae, for which the name Miniimonas arenae gen. nov., sp. nov. is proposed. The type strain of the type species is YM18-15T (=NBRC 106267T=KCTC 19750T=MBIC 08348T).